Evaluating the expression level of serum Interleukin-2, lipoarabinomannan and circulating MicroRNA-29a as diagnostic biomarkers for pulmonary and extra-pulmonary tuberculosis: a pilot study - Subhamay Adhikary; Sneha Leo; Antara Banerjee; Surajit Pathak; Meenakshi Narasimhan; Sridhar Rathinam (Annals of Medicine)
Background Diagnosis and treatment of Tuberculosis (TB), particularly delay in diagnosis of TB poses significant challenges in its eradication. The exploration of new biomarkers is urgently required for TB diagnosis and treatment. This study aimed to investigate the serum levels of Interleukin-2 (IL-2), an important diagnostic parameter in TB; lipoarabinomannan (LAM), a key constituent of the mycobacterial cell wall; and the expression of circulating microRNA-29a (miR-29a) in serum. MiR-29a contributes to increased susceptibility to TB by downregulating interferon-γ expression in T cells through post-transcriptional regulation, thereby exerting an immunosuppressive effect.Materials and methods The study was conducted on pulmonary TB (PTB), extra-pulmonary TB (EPTB), and control groups. Serum from the three groups was isolated, and IL-2 and LAM levels were measured by ELISA. Additionally, q-RT-PCR was conducted to analyse the expression of microRNA-29a in the serum of some TB patients.Result LAM and IL-2 were significantly upregulated in serum samples from both the PTB and EPTB groups compared to the control group. Additionally, the expression of miR-29a was significantly elevated in the EPTB group.Conclusion This study suggests that LAM and IL-2 may be potential diagnostic biomarkers for both PTB and EPTB, while miR-29a may be a promising marker specifically for EPTB. However, further evaluation with larger cohort samples is required to validate the clinical utility of LAM, IL-2, and miR-29a as diagnostic TB markers.